Determinan Harga Saham pada Perusahaan Sektor Industri yang Terdaftar Di Jakarta Islamic Index (JII) - Yulia Wati; Sugianto Sugianto; Muhammad Ikhsan Harahap (Universitas Nusantara PGRI Kediri, 2023)
This research aims to examine the effect of Economic Value Added (EVA), Net Profit Margin (NPM), Earning Per Share (EPS), and Return On Equity (ROE) on Industrial sector corporations listed in the Jakarta Islamic Index (JII) for the 2017-2021 period. This research uses the Eviews 9 App. The results of this research show that EVA, NPM and ROE have a positive and significant effect on Stock Price. While EPS has a positive and insignificant influence on the Share Price. And simultaneously all independent variables, namely EVA, NPM, EPS and ROE have a significant effect on stock prices in industrial sector corporations listed in the Jakarta Islamic Index (JII) for the 2017-2021 period. Based on the results of research with Eviews 9, it shows the value of the coefficient of determination (Adjusted R2) of the Stock Price is 0.404347. This means that 40.04% of the Share Price can be explained by the independent variables EVA, NPM, EPS and ROE. While the rest, namely 59.6%, was explained by external aspects of variables that were not included in this research.